The Effect Of Core Stability Exercise And Telephysiotherapy On The Walking Balance Of Post-Ischemic Stroke Patients - Sabirin Berampu; Siti Sarah Bintang; Syamsudin; Karnirius Harefa (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Stroke remains a major global health concern, ranking as the second leading cause of death and the third leading cause of disability worldwide. Among the common residual effects faced by stroke survivors is impaired walking balance. To address this issue, this study investigated the effectiveness of core stability exercises in improving walking balance, as measured by the Timed Up and Go (TUG) test. The study involved 12 participants aged between 40 and 70 years and adopted a case study approach. A quasi-experimental one-group pre-test and post-test design was used. The dependent variable was walking balance in post-ischemic stroke patients, while the independent variable was the implementation of core stability exercises delivered through tele-physiotherapy.Statistical analysis using the Shapiro-Wilk test revealed a significant improvement in walking balance after the intervention. The results showed a pre-intervention mean TUG score of 17.500 (SD = 5.351) and a post-intervention mean of 12.333 (SD = 3.228), with a significance value of 0.000 (df = 12). These findings indicate a statistically significant difference in performance before and after the intervention. In conclusion, the null hypothesis (H?) is rejected and the alternative hypothesis (H?) is accepted, demonstrating that core stability exercises delivered via tele-physiotherapy significantly improve walking balance in post-ischemic stroke patients at Budhi Dharma Clinic, Kreshna Foundation.